2013
DOI: 10.13172/2050-2303-2-1-326
|View full text |Cite
|
Sign up to set email alerts
|

Role of platelet-rich plasma in soft and hard connective tissue healing: an evidence-based review from basic to clinical application

Abstract: platelet-rich plasma is an effective conservative treatment without the complications and cost of surgery, and with moderate success of resolving various musculoskeletal conditions; however, it should not be placed in the first line of treatment modality because it is almost effective in the short term. Future clinical trial studies should be designed to test the real efficacy of platelet-rich plasma in a more standard manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(89 citation statements)
references
References 93 publications
(181 reference statements)
1
86
2
Order By: Relevance
“…The choice of the xenogeneic PRP presentation adopted in the present study contradicts the main scientific observations described 24,26 . According to these authors, xenogeneic PRP has a high immunogenic factor when compared to allogeneic and autogenic presentations.…”
Section: ■ Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…The choice of the xenogeneic PRP presentation adopted in the present study contradicts the main scientific observations described 24,26 . According to these authors, xenogeneic PRP has a high immunogenic factor when compared to allogeneic and autogenic presentations.…”
Section: ■ Discussioncontrasting
confidence: 79%
“…Contrary to previously mentioned 24,26 , no histopathological features were suggested that suggested an increase in bone resorption mediated by immunogenicity by xenogenic PRP. However, the preliminary result is considered and reliable inferences regarding the immune response to xenogeneic PRP are not possible.…”
Section: ■ Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Tissue engineering is another option which has been introduced in the last decade and currently it is the final option in managing large and massive tendon and ligament injuries [22][23][24][25][26][27][28][29][30][31][32]. Tissue engineering is defined as "a process that affects the structure and architecture of any viable and nonviable tissue with the aim to increase the effectiveness of the construct in biologic environments" [12].…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…All these available options have their own significant limitations [3]. Tissue engineering is a newer option and is divided into four categories of scaffold, healing promotive factors, stem cells and gene therapy [22][23][24][25][26][27][28][29][30][31][32]. Using each or a combination of them have provided the new insights in orthopedic surgery [12,24,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%